Quantifying Sodiation Kinetics in Alloying Tin Electrodes for Sodium-Ion Batteries. Issue 9 (24th September 2021) - Sarkar, Susmita; Verma, Ankit; Mukherjee, Partha P.
Abstract : Sodium-ion batteries (SIBs) are promising next-generation energy storage devices because of the elemental abundance and low sodium cost. However, the lower storage capacity and short lifespan of SIBs necessitate the need for a fundamental understanding of the sodiation/de-sodiation kinetics complexation due to the inherent electrode materials and electrolyte interactions. This study comprehensively studied the kinetics of the sodium alloying and de-alloying mechanism in tin (Sn) electrodes, a promising anode, relying on GITT-based (galvanostatic intermittent titration technique) analytics. This study includes a limited combinatorial analysis of sodium salts, namely, NaPF6 and NaClO4, in conjunction with different carbonate solvents. This comprehensive analysis elicits a comparative paradigm of diffusivity, charge transfer resistance, intercalation rate constant, and exchange current density for the salt/solvent combinations. Overall, NaClO4 exhibits better kinetic and transport properties as compared to NaPF6 . This study further elucidates the variation of ionic mobility and reaction rate with interfacial passivation due to excess fluorine donation from additives. The effect of active particle size reveals that nanoparticles exhibit reduced electrochemical (charge/discharge) hysteresis than microparticles. Overall, this study demonstrates a more considerable sensitivity of the charge transfer resistance, exchange current density, and reaction rate constants compared to the diffusivity.